2016
DOI: 10.1371/journal.pone.0149570
|View full text |Cite
|
Sign up to set email alerts
|

Skewed Differentiation of Circulating Vγ9Vδ2 T Lymphocytes in Melanoma and Impact on Clinical Outcome

Abstract: ObjectiveThe aim of this study was to evaluate over time circulating γδ T lymphocytes in melanoma patients in terms of frequency, effector functions, and relationship with clinical stage and evolution, by comparing preoperative values to those obtained at a mean follow-up of 36 months or in the event of recurrence or disease progression, and to those of healthy controls. Also, we correlated the presence of tumor-infiltrating γδ T lymphocytes with clinical evolution of melanoma.ResultsMean frequencies of circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…As for αβ Tc, there are many factors influencing the immunophenotypic features of γδ Tc. Upon stimulation, naïve γδ Tc can sequentially differentiate into T CM , T EM and T EMRA cells, thereby modifying the levels of CD45RA, CD45RO, CD27, CD28, CD197/CCR7 and other cell surface receptors [72,163,164]. In addition, once activated, γδ Tc modulate a wide range of cell surface activation-related molecules (e.g., CD69, CD25, CD28, CD38, CD45RO and HLA-DR) [165,166].…”
Section: Immunophenotypic and Functional Features Of Peripheral Bloodmentioning
confidence: 99%
“…As for αβ Tc, there are many factors influencing the immunophenotypic features of γδ Tc. Upon stimulation, naïve γδ Tc can sequentially differentiate into T CM , T EM and T EMRA cells, thereby modifying the levels of CD45RA, CD45RO, CD27, CD28, CD197/CCR7 and other cell surface receptors [72,163,164]. In addition, once activated, γδ Tc modulate a wide range of cell surface activation-related molecules (e.g., CD69, CD25, CD28, CD38, CD45RO and HLA-DR) [165,166].…”
Section: Immunophenotypic and Functional Features Of Peripheral Bloodmentioning
confidence: 99%
“…Infiltration of γδ T cells has been reported in many different tumour types including melanoma, ovary, colon, lung and prostate [123]. In melanoma patients, tumour infiltrating γδ T cells were significantly associated with lower mortality and relapse rates [124]. Additionally, patients who progressed to stage III or IV melanoma had a significantly decreased frequency of circulating Vγ9Vδ2 T cells.…”
Section: γδ T Cells and Cancermentioning
confidence: 95%
“…For instance, γδ T cells have demonstrated cytotoxic function against colon cancer and myeloma cells, (Wu et al 2015, von Lilienfeld-Toal et al 2006). Additionally, recent studies have suggested a cytotoxic role for Vδ9Vγ2 T cells in patients with melanoma; wherein an elevated frequency of circulating as well as tumor infiltrating Vδ9Vγ2 T cells in early stage tumors were correlated with decreased mortality and disease relapse (Toia et al 2016). Interestingly, however, it was observed that melanoma patients with a poor prognosis possessed a dramatically increased frequency of tumor-infiltrating Vδ9Vγ2 T cells in late stage disease.…”
Section: The Role Of γδ T Cells In Cancermentioning
confidence: 99%
“…Interestingly, however, it was observed that melanoma patients with a poor prognosis possessed a dramatically increased frequency of tumor-infiltrating Vδ9Vγ2 T cells in late stage disease. While no functional studies were performed, such observations may represent the acquisition of a suppressive phenotype due to modulation of the tumor microenvironment (Toia et al 2016). …”
Section: The Role Of γδ T Cells In Cancermentioning
confidence: 99%